2013
DOI: 10.1038/ni.2587
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transcriptional regulators in the mouse immune system

Abstract: The differentiation of hematopoietic stem cells into immune cells has been extensively studied in mammals, but the transcriptional circuitry controlling it is still only partially understood. Here, the Immunological Genome Project gene expression profiles across mouse immune lineages allowed us to systematically analyze these circuits. Using a computational algorithm called Ontogenet, we uncovered differentiation-stage specific regulators of mouse hematopoiesis, identifying many known hematopoietic regulators,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
199
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(207 citation statements)
references
References 38 publications
8
199
0
Order By: Relevance
“…Of the 81 gene sets defined by ImmGen that are associated with specific classes of immune and nonimmune cell types (coarse modules, as defined in ref. 19), 17 displayed significantly higher expression in catheterized mice compared with naive control animals (P adj < 0.05; corrected for number of modules tested, against the null hypothesis of no overall change in expression; Supplemental Figure 2 and Supplemental Table 5). These modules were associated with specific immune cell lineages, including DCs and granulocytes, consistent with the involvement of biological processes such as cell migration and motility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 81 gene sets defined by ImmGen that are associated with specific classes of immune and nonimmune cell types (coarse modules, as defined in ref. 19), 17 displayed significantly higher expression in catheterized mice compared with naive control animals (P adj < 0.05; corrected for number of modules tested, against the null hypothesis of no overall change in expression; Supplemental Figure 2 and Supplemental Table 5). These modules were associated with specific immune cell lineages, including DCs and granulocytes, consistent with the involvement of biological processes such as cell migration and motility.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we hypothesized that specific immune cell populations were present in the tissue and that genes associated with these populations would be prominently represented in the differentially expressed genes we observed to be upregulated in the catheterized state. We examined publicly available data from a compendium of immune cell types in C57BL/6J mice collected by the Immunological Genome Project (ImmGen) (19,20) and observed that this was indeed the case. Of the 81 gene sets defined by ImmGen that are associated with specific classes of immune and nonimmune cell types (coarse modules, as defined in ref.…”
Section: Resultsmentioning
confidence: 99%
“…Microarray comparisons of gene expression in B-cell subsets have identified Zfp318 as a member of a set of mRNAs that increases during maturation of immature B cells into mature follicular B cells (22)(23)(24). By analyzing flow-sorted B-cell subsets, we confirmed expression of Zfp318 mRNA closely parallels IgD heavy chain (Ighd) mRNA during B-cell development ( Two alternatively spliced isoforms of Zfp318 mRNA are annotated in the genome and described in the literature (18) (Fig.…”
Section: Identification Of a Missense Mutation In Zfp318 Causing Decrmentioning
confidence: 99%
“…One notable study examined gene coexpression in a several tissues separately and showed that such a tissue-specific approach was more efficient in predicting disease genes (12). Other efforts, such as the Immunological Genome Project (ImmGen) and ImmuNet, offer data-driven approaches for studying the immune system (13,14). However, low sample counts per cell type in the ImmGen dataset prohibit analysis of cell typespecific correlation of expression.…”
mentioning
confidence: 99%